THE PENGARUH TERAPI MUROTAL AL-QURAN TERHADAP TINGKAT KECEMASAN PASIEN PREOPERASI KATARAK DI RSUD PALABUHAN RATU: THE INFLUENCE OF MUROTAL AL-QURAN THERAPY ON THE ANXIETY LEVEL OF CATARACT PREOPERATION PATIENTS AT PALABUHAN RATU HOSPITAL - Nurlaelasari, Nonah (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2024)
Cataract is a clouding of the lens of the eye that can cause vision problems. Cataracts can be treated with surgery to remove the damaged lens and replace it with a new light-proof lens. Surgical procedures are a stressor for individuals and increase anxiety. Several approaches to intervening in patients with anxiety problems are pharmacological and non-pharmacological. There are many types and types of non-pharmacological approaches in accordance with the role and function of nurses, one of which is murottal therapy. Al Qur'an murottal therapy or Al Qur'an therapy is a distraction technique that can be used to overcome anxiety in patients. This study aims to determine the effect of Al-Quran murotal therapy on the anxiety level of pre-cataract surgery patients at Palabuhan Ratu Regional Hospital. The research method used was a pre-experimental method without a control group and the design of this research was to use only one group with a pretest and posttest. The results of the study showed that anxiety before undergoing Al-Qur'an murotal therapy was that a small percentage of respondents experienced mild anxiety at 5% and moderate anxiety at 93%. Anxiety after Al-Qur'an murotal therapy was that 100% of patients who would undergo pre-operation cataracts after being given Al-Qur'an murotal therapy did not feel anxiety. Then, the results of the Wilcoxon test showed that there was an influence of Al-Qur'an murotal therapy on the anxiety of pre-cataract surgery patients at Palabuhan Ratu Regional Hospital with a p value of 0.001. It is hoped that the results of the research can be input for nurses at the Palabuhan Ratu Regional Hospital, especially in the operating room, so that they can create an official SOP regarding finger grip relaxation, to be used as an alternative nursing action in dealing with anxiety